Cho \(a\) là một số thực dương. Rút gọn biểu thức $$P=\dfrac{\left(a^{\sqrt{7}-3}\right)^{\sqrt{7}+3}}{a^{\sqrt{11}-4}\cdot a^{5-\sqrt{11}}}.$$
\(P=\dfrac{1}{a^3}\) | |
\(P=a^3\) | |
\(P=a^2\) | |
\(P=a^{2\sqrt{7}-1}\) |
Chọn phương án A.
Dùng máy tính cầm tay: r \(a=2\) ta được $$P=\dfrac{1}{8}=\dfrac{1}{2^3}.$$Vậy \(P=\dfrac{1}{a^3}\).
Chọn phương án A.
\(\begin{aligned}
P&=\dfrac{\left(a^{\sqrt{7}-3}\right)^{\sqrt{7}+3}}{a^{\sqrt{11}-4}\cdot a^{5-\sqrt{11}}}\\
&=\dfrac{a^{\left(\sqrt{7}-3\right)\cdot\left(\sqrt{7}+3\right)}}{a^{\sqrt{11}-4+5-\sqrt{11}}}\\
&=\dfrac{a^{7-3^2}}{a}=\dfrac{a^{-2}}{a}=\dfrac{1}{a^3}.
\end{aligned}\)